2014
DOI: 10.1038/srep06356
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the pocketome of Mycobacterium tuberculosis and application in rationalizing polypharmacological target selection

Abstract: Polypharmacology is beginning to emerge as an important concept in the field of drug discovery. However, there are no established approaches to either select appropriate target sets or design polypharmacological drugs. Here, we propose a structural-proteomics approach that utilizes the structural information of the binding sites at a genome-scale obtained through in-house algorithms to characterize the pocketome, yielding a list of ligands that can participate in various biochemical events in the mycobacterial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 69 publications
(99 reference statements)
0
21
0
Order By: Relevance
“…Among our top scoring targets, many proteins broadly mentioned in the literature as signaling proteins (pnkB, pnkG, DevS) or related to mycolic acid synthesis (IhnA, pcaA, pks13, fas, fad32D), panthenoate biosynthesis (panB) and Cytochromes (cyp 121 and cyp125) have already been highlighted by Chandra's Lab and TDR Targets [75,25,85] as potential drug targets (shown in Table 4). Thus, as expected, there are some common ussual findings.…”
Section: What's Novel In Tb Targets?mentioning
confidence: 99%
“…Among our top scoring targets, many proteins broadly mentioned in the literature as signaling proteins (pnkB, pnkG, DevS) or related to mycolic acid synthesis (IhnA, pcaA, pks13, fas, fad32D), panthenoate biosynthesis (panB) and Cytochromes (cyp 121 and cyp125) have already been highlighted by Chandra's Lab and TDR Targets [75,25,85] as potential drug targets (shown in Table 4). Thus, as expected, there are some common ussual findings.…”
Section: What's Novel In Tb Targets?mentioning
confidence: 99%
“…On that account, a diverse dataset of small, drug-like molecules bound to high-quality models with accurately annotated pockets provides an invaluable resource for drug repositioning employing sequence order-independent pocket matching algorithms [ 40 43 ]. It is noteworthy that computational drug repurposing has suggested new opportunities to combat tuberculosis [ 44 , 45 ], malaria [ 46 ], and rare diseases [ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…The best-scoring pose of the cluster with the highest median score was selected and submitted to the PLIP web-server in order to analyse tuberculosis. Previous studies (46,47) have shown that this pathway is particularly exploited by Pseudomonas spp., which is able to use chlorinated compounds as sole carbon sources for nutrition, and this accounts for the prevalence of Pseudomonas in recreational waters.…”
Section: Psi-blast Of Mtbmentioning
confidence: 97%
“…The hotspots (43) and cavities (46) for ArgD were used to explore potential binding of two drugs, Amprenavir and Cochicine, to the ArgD protein and the putative interactions were investigated using a molecular docking approach. The structures of both ligands and of the pyridoxal 5' phosphate (PLP) cofactor were retrieved from Drugbank in the simplified molecular-input line-entry system (SMILES) format (47).…”
Section: Psi-blast Of Mtbmentioning
confidence: 99%